Computation of Thermal Radiative Flux from a Porous Medium by Using Fractal?Fractional Operator - Garalleh H.A.L.; Ramzan M.; Shafique A.; Abbas S.; Nazar M.; Jan R. (Springer, 2025)
Fractal?fractional derivative has numerous significance in real world problems. The main goal of this derivative is the use of memory effects to formulate the model. Due to extensive applications of fractional derivatives, in the present article fractional order model of Brinkman fluid has been analyzed. The governing equations of the present flow model are solved numerically by using Cranck-Nicolson method to obtain the solutions for mass, energy, and momentum equations. In additions the physical aspects of material and flow parameters like as Prandtl number, magnetic force, Schmidt number, Grashof thermal number, Grashof mass number, especially the fractional operators are studied by drawing the graphs of field of interest. ? The Author(s), under exclusive licence to Springer Nature India Private Limited 2024.